Phase Correcting Element for Intra-Cavity Laser Beam Control - Lau, F. K. (Institutional Knowledge at Singapore Management University, 2006)
A novel semiconductor laser cavity concept comprising an integrated phase correcting element is proposed and demonstrated. Characterization of the design for divergence angle reduction and near-field broadening revealed an improvement of 30.8% and 10.8%, respectively.